Enhanced electrical and energy storage performances of Fe, Sb co-doped BNBCTS ceramics synthesized via the solid-state combustion technique - Kornphom, C.; Saenkam, K.; Yotthuan, S.; Vittayakorn, N.; Bongkarn, T. (My University, 2024)
In this study BNBCTS ceramics were co-doped with Fe and Sb to form (Bi0.5Na0.5)0.93(Ba0.945Ca0.055)0.07(Ti(0.9946-x)Sn0.0054)(Fe0.5Sb0.5)xO3 ceramics (denoted as BNBCTS-xFS) with various x content and were prepared via the solid-state combustion technique to enhance the electrical and energy storage performance. The effect of co-doping Fe and Sb on the phase formation, defect dipole, microstructure, electrical and energy storage properties of BNBCTS-xFS ceramics was studied. When x content increased from 0.0 to 0.030, the amount of the rhombohedral (R) phase decreased from 51 to 24 % while the tetragonal (T) phase increased from 49 to 76 %. The increased Fe and Sb content increased the defect dipole of singly/doubly charged oxygen-vacancies (VO∙/ VO∙∙) and caused more Ti4+ to transition to Ti3+, which caused the transition temperature of the ferroelectric phase to relaxor state (TF-R) in the ceramics to drop to below room temperature and it exhibited relaxor characteristics at room temperature. The ceramic with an x content of 0.010 had the largest grain size (3.06 μm), excellence ferroelectric properties (Pr ∼31.04 μC/cm2, Pm ∼38.98 μC/cm2 and Ec ∼18.28 kV/cm), the largest electro strain (∼0.175 %) and a large d33* of 350 pm/V. Moreover, when x = 0.020, the ergodic relaxor ceramic showed the smallest grain size (1.03 μm), the lowest remanant polarization (Pr) of 4.52 μC/cm2 and the lowest coercive field (Ec) of 8.37 kV/cm, at an electric field of 60 kV/cm. More importantly, energy storage properties at the electric breakdown strength (Eb = 120 kV/cm) of the ceramics with an x content of 0.020 exhibited a recoverable energy storage density (Wrec) of 1.81 J/cm3, a total energy storage density (Wtotal) of 2.95 J/cm3 and an efficiency (η) of 61.30%, with excellent thermal (∼25–150 °C) and frequency stability (∼1–100 Hz). This study provides new insights into the modulation of BNBCTS ceramics with Fe and Sb co-doping, which could effectively improve the electrical properties and energy storage properties of BNBCTS-xFS ceramics.
Keywords: BNT-based ceramics; Energy storage; Oxygen vacancy; Phase formation; Piezoelectric